Osteocytes and Bone Metastasis - Riquelme, Manuel A.; Cardenas, Eduardo R.; Jiang, Jean X. (Frontiers in Endocrinology, 2020)
Bone is the most frequent site of breast and prostate cancer, and one of the most common sites of metastasis for many solid tumors. Once cancer cells colonize in the bone, it imposes a major clinical challenge for the treatment of the disease and fatality rates increase drastically. Bone provides a fertile microenvironment enriched with nutrients, growth factors and hormones, a generous booty for cancer cells. The osteocyte, which is the most abundant cell type (~ 95%) in the bone, is the primary cell responsible for bone homeostasis. Embedded inside the bone mineral matrix, osteocytes are connected and able to sense and respond coordinately to environmental cues, such as hormones, physical stress, and mechanical loading and unloading. These properties allow osteocytes to modulate the bone microenvironment by promoting the release of factors that regulate bone function and homeostasis. Cancer cells have the ability to hijack and influence the bone microenvironment. Cancer cells can cause osteoblastic (bone forming) or osteolytic lesions to promote the net resorption or release of growth factors from the bone extracellular matrix. These processes activate a “vicious cycle”, leading to disruption of bone integrity and promoting cancer cell growth and migration. To achieve this, cancer cells have to colonize and take over the intrinsic defense mechanism presented by osteocytes. Osteocytes can release anti-cancer factors, such as ATP, that inhibit breast cancer cells metastasis. In this review, we will summarize recent research findings and provide mechanistic insights related to the role of osteocytes in cancer bone metastasis.